IS15DIV-flanked composite transposon harboring blaNDM-5 in multidrug-resistant Salmonella Typhimurium - Kaiting Zhao; Jing Jin; Yuan Liao; Aixia Liu; Wugao Liu; Weiping Wu (iScience)
Summary: Multidrug-resistant Salmonella Typhimurium has emerged as a global public health concern. Asymptomatic gastrointestinal carriage is a key factor in the spread of antibiotic-resistant bacteria. However, it is challenging to obtain direct evidence of in vivo transfer of mobile genetic elements (MGEs). Here, we found that MGEs harboring blaNDM-5 were transferred from asymptomatic Escherichia coli (LS20223694) to Salmonella Typhimurium (LS20223695) in a child. BLAST analyses demonstrated that the IS15DIV-flanked composite transposon of pLS20223695_NDM5 showed high similarity with pLS20223694_NDM5 and two previously reported plasmids, suggesting the possibility of genetic recombination. Besides, conjugation experiments showed that the transconjugant carried the incompatibility group I1 (IncI1)-I(alpha) plasmid replicon with the blaNDM-5 and sul1 genes, indicating that pLS20223695_NDM5 is a conjugative plasmid with transferability. Our study provides insights into the genetic basis of an IS15DIV-flanked composite transposon in Salmonella Typhimurium.